KELIMPAHAN DAN DISTRIBUSI TIGA JENIS IKAN BOTIA DI DAS SIBAU DAN DAS EMBALOH, KAPUAS, KALIMANTAN BARAT (Abundance and distribution of three species of Botia in Sibau and Embaloh Watershed) - Rachmatika, Ike (Research Center for Biology-Indonesian Institute of Sciences, 1998)
The study on the abundance and distribution of three species of botia namely B.hymenophysa Bleeker, B.macracantha (Bleeker,1852)W B.reversa (Roberts,1989) was conducted in Sibau watershed (from June 21 to July 10 1996) and in Embaloh watershed (from November 21 to December 10,1996 and from September 5 to September 25, 1997).It was found that the abundance of each B.hymenophysa, B.macracantha andB.tevctsz was not significant different in these two watershed.Among the fish species collected, these three species of Botia can b categorized as the group offish with low abundance.B.hymenophysa is the most widely distributed fish among three species o/Botia in these two watersheds.In these watersheds,this fish was more distributed in tributary sites than in mainstream sites of Embaloh and Sibau river.On the other hand, the distribution pattern of B.reversa in these watersheds was different. In Sibau watershed, this fish is more distributed in mainstream sites, in Embabh watershed however, this fish was more distributed in tributaries sites.In some localities the distribution of B.hymenophysa and B.reversa are overlaps. In Sibau river, B.macracantha was found both in mainstream sites and its tributary, but in Embabh river, it was found only in a tributary site. It was also found that these three Botia could co-exist with other species.